Anatomy and histology of the external and internal reproductive organs in the male and female false codling moth, Argyroploce Leucotreta Meyr. (Lepidoptera) - Swart, P. L.(Philippus Lodewikus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric) -- University of Stellenbosch, 1966.